Mainstreaming Mental Health Care in 42 Countries. Issue 4 (2nd October 2017) - Shen, Gordon C.; Eaton, Julian; Snowden, Lonnie R.
Abstract : Abstract —Global consensus and national policies have emphasized deinstitutionalization, or a shift in providing mental health care from institutional to community settings. Yet, psychiatric hospitals and asylums receive the majority of mental health funding in many countries, at odds with research evidence that suggests that services should be delivered in the community. Our aim is to investigate the norms, actors, and strategies that influence the uptake of deinstitutionalization internationally. Our study is informed by prior literature on management and implementation science. The success and failure of mental health care operations depend on identifying and overcoming challenges related to implementing innovations within national contexts. We surveyed 78 experts spanning 42 countries on their knowledge and experiences in expanding community-based mental health care and/or downsizing institution-based care. We also asked them about the contexts in which said methods were implemented in a country. We found that mental health care, whether it is provided in institutions or in the community, does not seem to be standardized across countries. Our analysis also showed that moving deinstitutionalization forward requires meaningful engagement of three types of actors: government officials, health care professionals, and local experts. Progress toward deinstitutionalization depends on the partnerships formed among these actors and with diverse stakeholders, which have the potential to garner resources and to scale-up pilot projects. In conclusion, different countries have adapted deinstitutionalization in ways to meet idiosyncratic situations and population needs. More attention should be given to the management and implementation strategies that are used to augment treatment and preventive services.